Uniaxial and biaxial strain engineering in 2D MoS2 with lithographically patterned thin film stressors - Azizimanesh, Ahmad; Peña, Tara; Sewaket, Arfan; Hou, Wenhui; Wu, Stephen M. (Applied physics letters, 2021)
We introduce a controllable approach to selectively strain (uniaxially or biaxially) MoS2 by depositing e-beam evaporated thin film stressors with a lithographically patterned stripe geometry. This type of strain engineering has been highly successful in commercial silicon-based CMOS processes to enhance carrier mobility by applying uniaxial strain in MOSFET channels. We attempt to outline the basis for using the same techniques with 2D van der Waals materials with weak out-of-plane bonding. The stressor in this work is chosen to be optically transparent to examine the strain distribution within MoS2 using Raman spectroscopic mapping. MoS2 flakes with partial tensile stressor coverage show large tensile strains close to free edges and compressive strain at the center of the stressor strip. Both in-plane and out-of-plane strains are observed. By varying strip width and MoS2 flake thickness, the geometric distribution of both tensile and compressive strained regions can be controlled. The directionality of strain induced by the stressor strip is also explored through polarized Raman spectroscopy where MoS2 shows 0.85% uniaxial strains occurring at strip edges for 25 N/m film force and biaxial strains occurring at strip centers using the same stressor. Using these combined techniques, we show that strain in 2D materials can be uniquely engineered by design to selectively exhibit tension/compression, uniaxiality/biaxiality, and directionality relative to crystal axes through simple lithographic patterning of stressed thin films. This opens the opportunity to create strain patterned devices with a wide variety of strain-tunable 2D materials properties (electronic, optical, superconducting, etc.), now controllable by micro/nanolithographic design.